Changes in some physicochemical properties of Cassia seiberiana seeds during roasting (2012)
"One of the uses of Cassia sieberiana seeds is roasting for beverage. Therefore, the thrust of this work was to study changes in some physicochemical properties of Cassia sieberiana seeds during roasting. A 3 x 3 factorial experimental design was employed. Roasting temperatures were 190, 210 and 230°C while roasting times were 10, 20 and 30 min respectively. Nine experimental combinations were produced. Proximate composition of unroasted sample, pH, total soluble solid, total titratable acidity, acetic acid, weight loss, caffeine content, swelling and colour of both unroasted and roasted samples were determined using standard methods. Proximate composition of unroasted Cassia sieberiana in percentage as determined were moisture content (9.04 ± 0.04), ash (9.3 ± 0.03), crude fibre(16.21 ± 0.09); crude protein(19.88 ± 0.03), fat (5.31 ± 0.05) and carbohydrate (40.26 ± 0.33). The pH, total soluble solid, total titratable acidity, acetic acid, caffeine content and colour of unroasted Cassiasieberiana seed-were 6.25 ±0.7, 3.0 ± 0.13 (oO), 0.57 ± 0.06 (mg/g), 0.12 ± 0.00 (%), 11.6 ± 1.05 (%) and 0.43 abs respectively. Effect of roasting was significant (p < 0.05) on moisture content, weight loss, caffeine content, swelling and colour, while a non-significant (p > 0.05) effect was recorded on pH, total soluble solid, total titratable acidity and acetic acid."